2020
DOI: 10.3389/fonc.2020.584607
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Advanced Chronic Lymphoid Leukemia Unveiled by Single-Cell Transcriptomics: A Case Report

Abstract: Genetic and transcriptional heterogeneity of Chronic lymphocytic leukaemia (CLL) limits prevention of disease progression. Longitudinal single-cell transcriptomics represents the state-of-the-art method to profile the disease heterogeneity at diagnosis and to inform about disease evolution. Here, we apply single-cell RNA-seq to a CLL case, sampled at diagnosis and relapse, that was treated with FCR (Fludarabine, Cyclophosphamide, Rituximab) and underwent a dramatic decrease in CD19 expression during disease pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
2
0
1
Order By: Relevance
“… 18 It is diagnosed based on a blood smear and immunophenotyping by flow cytometry, although advanced studies have found that single-cell profiling of CLL at diagnosis can give the best treatment. 18 Among all cases, CLL was found to rank third, with a total of 25 cases, accounting for 11.9% of the total. This subtype was ranked the fifth in a study conducted between 1999-2013, where it constituted 8.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 18 It is diagnosed based on a blood smear and immunophenotyping by flow cytometry, although advanced studies have found that single-cell profiling of CLL at diagnosis can give the best treatment. 18 Among all cases, CLL was found to rank third, with a total of 25 cases, accounting for 11.9% of the total. This subtype was ranked the fifth in a study conducted between 1999-2013, where it constituted 8.6% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…16 Chronic lymphoid leukemia (CLL) is reportedly most common in the western world, particularly among the elderly, and is characterized by increased lymphocytes in the bone marrow and blood. 18 It is diagnosed based on a blood smear and immunophenotyping by flow cytometry, although advanced studies have found that single-cell profiling of CLL at diagnosis can give the best treatment. 18 Among all cases, CLL was found to rank third, with a total of 25 cases, accounting for 11.9% of the total.…”
mentioning
confidence: 99%
“…Um escore elevado de comorbidades influenciou negativamente na sobrevida relativa dos pacientes, mas sem efeito estatisticamente significativo na mortalidade (38) . Outro estudo semelhante, no entanto, identificou que pacientes idosos com disfunções renais possuíram mau prognóstico sob tratamento com fludarabina (39) .…”
Section: Questõesunclassified